Pengaruh Model Pembelajaran Kooperatif Tipe Talking Chips Terhadap Keterampilan Komunikasi Siswa Kelas IV UPT SD Negeri 22 Gresik - Firdawati Ilham; Arya Setya Nugraha (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
The Influence of the Talking Chips Cooperative Learning Model on the Communication Skills of Class IV Students of UPT SD Negeri 22 Gresik. Thesis, Elementary School Teacher Education Study Program. Faculty of Teacher Training and Education. Muhammadiyah University of Gresik (Supervised by Arya Setya Nugraha, M.Pd and Nanang Khoirul Umam, M.Pd). This study aims to determine the effect of the talking chips type cooperative learning model on the communication skills of fourth grade elementary school students in the 2021/2022 academic year. The method used in this study is an experimental method using the Nonequivalent Control Group Design research design. The subjects in this study were students in grades IV-A and IV-B at UPT SD Negeri 22 Gresik with the same number of students, namely 20 students. Data collection techniques in this study were using observation sheets and oral tests of communication skills. Analysis of the data obtained, namely the results of communication skills prove that there is a difference after being given a test to the control class and the experimental class. It is proven by the results of the post-test score for the control class of 74.75. While the results of the post-test value of the experimental class is 87.75. Hypothesis testing in this study using the independent sample T-test obtained significant results, namely 0.000 <0.05, it can be concluded that there is an effect of the talking chips type cooperative learning model on the communication skills of fourth grade students of UPT SD Negeri 22 Gresik. Keywords: Talking Chips Type Cooperative Model, Communication Skills